2008
DOI: 10.1044/1092-4388(2008/07-0083)
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trajectories of the Development of Speech Sound Production in Pediatric Cochlear Implant Recipients

Abstract: Purpose This study characterized the development of speech sound production in prelingually deaf children with a minimum of 8 years of cochlear implant (CI) experience. Method Twenty-seven pediatric CI recipients' spontaneous speech samples from annual evaluation sessions were phonemically transcribed. Accuracy for these speech samples was evaluated in piecewise regression models. Results As a group, pediatric CI recipients showed steady improvement in speech sound production following implantation, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 25 publications
4
46
1
1
Order By: Relevance
“…Nittrouer, Caldwell, Lowenstein, Tarr, and Holloman (2012) found that comprehension of spoken language was the best predictor, in children below 24 months of age, of their language/literacy skills in kindergarten. Tomblin et al (2008) found that accuracy of speech sound production at 4 years postimplant was a good predictor of speech skills after 5 to 10 years of use. Moeller et al (2007) studied speech sound development between 10 and 24 months of age in 33 children with and without hearing loss and found that early measures of syllable production predicted unique variance in later speech production and vocabulary outcomes.…”
Section: Predicting Language Delay In Children With Cismentioning
confidence: 99%
See 2 more Smart Citations
“…Nittrouer, Caldwell, Lowenstein, Tarr, and Holloman (2012) found that comprehension of spoken language was the best predictor, in children below 24 months of age, of their language/literacy skills in kindergarten. Tomblin et al (2008) found that accuracy of speech sound production at 4 years postimplant was a good predictor of speech skills after 5 to 10 years of use. Moeller et al (2007) studied speech sound development between 10 and 24 months of age in 33 children with and without hearing loss and found that early measures of syllable production predicted unique variance in later speech production and vocabulary outcomes.…”
Section: Predicting Language Delay In Children With Cismentioning
confidence: 99%
“…Over the years, updates in CI technology have included redesigned internal equipment (i.e., electrode arrays and internal receiver stimulators), new speech processing strategies, and external device hardware (speech processors and microphones; Carlson, Driscoll, Gifford, & McMenomey, 2012;Wilson & Dorman, 2008). For example, early improvements in speech processing strategies resulted in significant improvements in speech perception for adults and children (Geers, Brenner, & Davidson, 1999;Skinner, Arndt, & Staller, 2002;Skinner et al, 1994;Tomblin, Peng, Spencer, & Lu, 2008;Wilson & Dorman, 2008). Improved front-end processing strategies and microphone and processor technology have combined to improve speech perception, especially for access to low-level speech inputs (Davidson, 2006;Dawson, Decker, & Psarros, 2004;Dawson, Vandali, Knight, & Heasman, 2007).…”
Section: Predicting Language Delay In Children With Cismentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies that have analyzed the speech of children with cochlear implants (CIs) have examined how intelligible these children are (e.g., Chin et al, 2003;Peng et al, 2004) or how accurately they produce phonemes (e.g., Blamey et al, 2001;Tobey et al, 2007;Tomblin et al, 2008). While these studies have generally observed that children with CIs have poorer speech production than is expected from their peers with normal hearing (NH), their conclusions are limited by the fact that accuracy and intelligibility are based solely on adult listeners' judgments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that speech intelligibility of children with profound hearing loss improved after cochlear implantation [6][7][8][9][10], and improved with increased duration of implant use [11]. Younger age of implantation was also associated with higher levels of intelligibility for children with profound hearing loss [12].…”
Section: Introductionmentioning
confidence: 99%